Long-term effect of intensive cultivation with imbalanced use of fertilizers and manures on loamy sand alluvial soils and nutrient status of growing wheat in Lukhi soil series of north-western India. (23rd August 2016) - Singh, Komal; Bansal, S. K.
ABSTRACT: Long-term effects of intensive cultivation and imbalanced fertilization were studied on nutrient concentration of soil and in wheat grown on loamy sand alluvial soils belonging to Lukhi soil series located in semiarid-subtropical region of North-Western India. The same 86 farmers' fields were sampled during 2009 and 2010 which had earlier been studied during 1983 and 1984. Electrical conductivity of soil decreased, pH did not change, and organic carbon improved. In soil, K extractable in 1N NH4OAc and boiling 1N HNO3 depleted to a deficient levels in 2009 from medium levels of 1983. Similarly, DTPA extractable Cu depleted to deficient level from earlier sufficient level in 2009 from medium K and sufficient Cu levels in 1983. Consequently, K and Cu in the top two leaves of wheat decreased to a deficient level in 2010 from a sufficient level in 1984. Sulfur in soils and leaves decreased significantly. Olsen P and DTPA-extractable Zn increased, increasing their contents in leaves. DTPA-extractable manganese (Mn) and iron (Fe) improved.